Establishment of an efficient and wide-spectrum droplet-vitrification cryopreservation for raspberry (Rubus idaeus L.) germplasm and assessments of genetic integrity and vegetative growth in the regenerants - Xiao-Yan Ma; Dag‑Ragnar Blystad; Qiao-Chun Wang; Lu Tong; Øyvor Stensbøl; Dong Zhang; Zhibo Hamborg (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)
By optimizing size of shoot tips, preculture medium and exposure duration to PVS2, we established an efficient and wide-spectrum droplet-vitrification cryopreservation for shoot tips of raspberry ( Rubus idaeus L.). This protocol yielded 80–100% and 67–100% of survival and shoot regrowth levels in cryopreserved shoot tips across 23 raspberry genotypes. Genetic integrity was assessed in cryo-derived regenerants after 3 months of post-cryopreservation using inter simple sequence repeat (ISSR), single nucleotide polymorphism (SNPs), and insertions and deletions (InDels). ISSR did not detect any polymorphic bands in the cryo-derived regenerants. Although the number of SNPs and InDels decreased in the cryo-derived regenerants, variation trends were similar between the cryo-derived regenerants and the control. Plant vegetative growth and root growth were assessed in the cryo-derived plants after 9 weeks of growth in greenhouse. There were no significant differences in plant vegetative growth measured by plant height, number of fully-opened leaved, leaf area, and fresh and dry weight between the cryo-derived plants and the control, although significant differences were observed in root growth measured by root total length, root average diameter and root volume between the two types of plants. The results obtained in the present study indicate that the droplet-vitrification method has great potential for cryopreservation of raspberry germplasm.

The species, density, and intra-plant distribution of mites on red raspberry (Rubus idaeus L.) - Jiunn Luh Tan; Nina Trandem; Zhibo Hamborg; Bijaya Sapkota; Dag-Ragnar Blystad; Jana Fránová; Rostislav Zemek (Experimental and Applied Acarology, 2024)
The adoption of the European Green Deal will limit acaricide use in high value crops like raspberry, to be replaced by biological control and other alternative strategies. More basic knowledge on mites in such crops is then necessary, like species, density, and their role as vectors of plant diseases. This study had four aims, focusing on raspberry leaves at northern altitude: (1) identify mite species; (2) study mite population densities; (3) investigate mite intra-plant distribution; (4) investigate co-occurrence of phytophagous mites, raspberry leaf blotch disorder and raspberry leaf blotch virus (RLBV). Four sites in south-eastern Norway were sampled five times. Floricanes from different parts of the sites were collected, taking one leaf from each of the upper, middle, and bottom zones of the cane. Mites were extracted with a washing technique and processed for species identification and RLBV detection. Mites and leaves were tested for RLBV by reverse transcription polymerase chain reaction (RT-PCR) with virus-specific primers. Phytophagous mites, Phyllocoptes gracilis , Tetranychus urticae , and Neotetranychus rubi , and predatory mites, Anystis baccarum and Typhlodromus ( Typhlodromus ) pyri were identified. All phytophagous mites in cultivated raspberry preferred the upper zone of floricanes, while in non-cultivated raspberry, they preferred the middle zone. The presence of phytophagous mites did not lead to raspberry leaf blotch disorder during this study. RLBV was detected in 1.3% of the sampled plants, none of them with leaf blotch symptoms, and in 4.3% of P. gracilis samples, and in some spider mite samples, implying that Tetranychids could also be vectors of RLBV.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Assessments of rooting, vegetative growth, bulb production, genetic integrity and biochemical compounds in cryopreserved plants of shallot - Min-Rui Wang; Zhibo Hamborg; Rune Slimestad; Abdelhameed Elameen; Dag-Ragnar Blystad; Sissel Haugslien; Gry Skjeseth; Qiao-Chun Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2021)

Droplet-vitrification for shoot tip cryopreservation of shallot (Allium cepa var. aggregatum): effects of PVS3 and PVS2 on shoot regrowth - Min-Rui Wang; Zhibo Zhang; Jiří Zámečník; Alois Bilavčík; Dag-Ragnar Blystad; Sissel Haugslien; Qiao-Chun Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Growth, microtuber production and physiological metabolism in virus-free and virus-infected potato in vitro plantlets grown under NaCl-induced salt stress - Jing-Wei Li; Hai-Yan Chen; Jiao Li; Zhibo Zhang; Dag-Ragnar Blystad; Qiao-Chun Wang (European Journal of Plant Pathology, 2018)

Cryopreservation and evaluations of vegetative growth, microtuber production and genetic stability in regenerants of purple-fleshed potato - Jing-Wei Li; Hai-Yan Chen; Xiao-Yue Li; Zhibo Zhang; Dag-Ragnar Blystad; Qiao-Chun Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Field performance evaluation and genetic integrity assessment in Argyranthemum ‘Yellow Empire’ plants recovered from cryopreserved shoot tips - Zhibo Zhang; Gry Skjeseth; Abdelhameed Elameen; Sissel Haugslien; Astrid Sivertsen; Jihong Liu Clarke; Qiao-Chun Wang; Dag-Ragnar Blystad (In Vitro Cellular & Developmental Biology - Plant, 2015)

Host range and symptomatology of Pepino mosaic virus strains occurring in Europe - Dag-Ragnar Blystad; René van der Vlugt; Ana Alfaro-Fernández; María del Carmen Córdoba; Gábor Bese; Dimitrinka Hristova; Henryk Pospieszny; Nataša Mehle; Maja Ravnikar; Laura Tomassoli; Christina Varveri; Steen Lykke Nielsen (European Journal of Plant Pathology, 2015)

Seed transmission of Pepino mosaic virus in tomato - Inge M. Hanssen; Rick Mumford; Dag-Ragnar Blystad; Isabel Cortez; Beata Hasiów-Jaroszewska; Dimitrinka Hristova; Israel Pagán; Ana-Maria Pereira; Jeff Peters; Henryk Pospieszny; Maja Ravnikar; Ineke Stijger; et al. (European Journal of Plant Pathology, 2010)

Symptomless infectious cDNA clone of a Norwegian isolate of Poinsettia mosaic virus - Carl Spetz; Roar Moe; Dag-Ragnar Blystad (Archives of Virology, 2008)

Agrobacterium tumefaciens-mediated transformation of poinsettia, Euphorbia pulcherrima, with virus-derived hairpin RNA constructs confers resistance to Poinsettia mosaic virus - Jihong Liu Clarke; Carl Spetz; Sissel Haugslien; Shaochen Xing; Merete W. Dees; Roar Moe; Dag-Ragnar Blystad (Plant Cell Reports, 2008)